Exploring Buginese ethnomathematics in Saoraja La Tenri Bali to foster cultural intelligence - Aras, Andi; Sudirman, Sudirman; Zahrawati B, Fawziah (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Mathematics is often taught without sufficient cultural context, resulting in limited relevance and student disengagement. To address this issue, integrating ethnomathematics into mathematics instruction is essential for enhancing both mathematical understanding and cultural intelligence. This study explores the mathematical concepts embedded in the architectural design of the Saoraja La Tenri Bali, a traditional Buginese house, and examines its potential as a culturally grounded learning resource. Using a qualitative descriptive design with an ethnographic approach, data were collected through observations, documentation, and in-depth interviews, and analysed using Spradley’s ethnographic model. The findings identify various mathematical concepts, including linear equations (parallel, intersecting, and perpendicular lines) and geometric transformations (reflection, translation, rotation, and dilation), reflected in the house’s architectural structure. These mathematical elements are closely intertwined with Buginese philosophical values such as sipakalebbi, sipakaraja, sipakatau, and sipakainge, which emphasise mutual respect and social harmony. The study highlights that integrating traditional architecture into mathematics education can strengthen mathematical reasoning while fostering students’ cultural intelligence. Therefore, culturally responsive learning models that incorporate local wisdom are recommended to support both academic achievement and intercultural competence.